The Effect of Product Variety, Brand Image and Social Media Marketing on Repurchase Interest in Fashion Wearmade Products - Arista Dewi, Ni Putu Mirah; Atmaja, Ni Putu Cempaka Dharmadewi; Mane, Daniel (Journal of International Conference Proceedings, 2024)
There are many factors that encourage and become consumer considerations in terms of buying interest that is always changing and tends to follow the trends that are happening. In this case, the company must know the trend that occurs so that consumers intend to buy again. This study aims to determine the influence of product variation, brand image and social media marketing on repurchase interest in Wearmade fashion products. The number of samples used was 112 respondents who were Wearmade consumers who had made purchases by sampling using the purposive sampling technique using the hair formula. The data was taken with a Likert scale questionnaire and processed using the Statistical Program for Social Science (SPSS). The results of the study prove that product variation has a positive and significant effect on repurchase interest, Brand image has a positive and significant effect on repurchase interest, and social media marketing has a positive and significant effect on repurchase interest.